2005
DOI: 10.1093/aje/kwi289
|View full text |Cite
|
Sign up to set email alerts
|

Community Clusters of Childhood Leukemia and Lymphoma: Evidence of Infection?

Abstract: Information suggesting that infection may be an underlying cause of childhood leukemia and lymphoma includes the occasional appearance of cases in time-space clusters within communities and increased incidence after communities experience marked population influxes (population mixing). Among 50 clusters involving cases of childhood leukemia and lymphoma investigated in the United States in 1961-1977, eight showed suggestive evidence of underlying infectious causation. In seven of the eight communities, case oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Numerous such investigations of childhood leukemia have been conducted without any firm conclusions as to causality. 86,87 A major reason is the so-called "Texas Sharpshooter Effect," in which one shoots first and draws a bull's-eye around the bullet holes subsequently. 88 Spatiotemporal boundaries are often specified post hoc, making it seem that disease incidence is unusually high.…”
Section: Epidemiologic Methods In Childhood Leukemia Researchmentioning
confidence: 99%
“…Numerous such investigations of childhood leukemia have been conducted without any firm conclusions as to causality. 86,87 A major reason is the so-called "Texas Sharpshooter Effect," in which one shoots first and draws a bull's-eye around the bullet holes subsequently. 88 Spatiotemporal boundaries are often specified post hoc, making it seem that disease incidence is unusually high.…”
Section: Epidemiologic Methods In Childhood Leukemia Researchmentioning
confidence: 99%
“…The incidence is lowest in North Africa and the Middle East, and highest in the industrialized Western countries, suggesting that this may reflect more exposure to environmental leukemogens [6]. Numerous investigators have reported the occurrence of leukemic clusters in different geographic areas, thus pointing towards infectious and/or environmental causes of at least some cases of ALL [14][15][16][17]. Several studies have suggested a link between maternal reproductive history and the risk of ALL.…”
Section: Epidemiologymentioning
confidence: 99%
“…Clusters of childhood leukemia have been shown not only in the vicinity of nuclear installations [16] but also in other locations [17]. Incidence of childhood leukemia has been increasing since the end of 1970 in the developed countries [18].…”
Section: Discussionmentioning
confidence: 99%